The Effects of Dance and Dance Movement Therapy on Children with Autism Spectrum Disorder: A Narrative Review - Pagacz, Katarzyna; Kolasa, Wiktoria; Stadnik, Aleksandra; Lis, Monika; Jędryka, Maria; Kaczorek, Marta; Gatniejewska, Julia; Kowalczyk, Olga; Kiełbasa, Bożena (Quality in Sport, 2026)
Background. Autism spectrum disorder (ASD) is one of the most common neurodevelopmental disorders. Alongside standard therapeutic methods, there is growing interest in non-pharmacological interventions that support the development of children with ASD. One such intervention is Dance Movement Therapy (DMT), which is a multidimensional form of activity combining movement, music, emotional expression and social interaction. In recent years, an increasing number of studies have been published on the impact of both dance and DMT on the functioning of children with ASD. The results of these studies are promising and offer hope for supporting the development of these children. Aim. The aim of this narrative review is to present and analyse the current scientific literature on the impact of dance and DMT on the functioning of children with autism spectrum disorders. Material and methods. This study is a narrative review of the scientific literature on the impact of dance and DMT on the functioning of children with ASD. The literature search was conducted in the PubMed database and on the ResearchGate platform using the following keywords: ‘autism spectrum disorder’, ‘ASD’, ‘dance’ and ‘dance movement therapy’. Results. The studies analysed indicate that dance and Dance Movement Therapy (DMT) improve the functioning of children with ASD. The beneficial outcomes relate primarily to social skills, communication, emotional regulation, sensory-motor integration, as well as a reduction in repetitive behaviours. At the same time, the therapeutic effects achieved can lead to an improvement in the quality of life for these children and their families. Conclusions. Dance and Dance Movement Therapy (DMT) appear to be a promising form of therapeutic support for children with autism spectrum disorder (ASD). Owing to its accessible, engaging and child-friendly nature, DMT may serve as an effective and valuable complement to the therapeutic process.